Challenges and Opportunities of Using ChatGPT in Elementary School Learning: A Study of Teacher Ethics and Morals in Supporting the Independent Curriculum - Dinda Ramadhani; Tri Nanda Syafitri; Nur Wahyuni (Outline Journal of Education, 2025)
The rapid development of technology has transformed the learning paradigm in elementary schools (SD), especially through artificial intelligence (AI). The use of AI, particularly ChatGPT, offers opportunities for more interactive, personalized, and adaptive learning. This aligns well with the values of the Merdeka Curriculum, which promotes freedom of learning and the strengthening of student character. However, the use of this technology also presents challenges, particularly in terms of ethics and morality, which must be addressed by teachers as facilitators and educators in elementary schools. This study was conducted through a systematic literature review approach by gathering various recent research sources in the fields of educational ethics and morality, artificial intelligence, and educational curriculum. The results of the analysis indicate that teachers must be prepared to manage technology responsibly in order to maximize benefits and minimize risks such as technology dependence, plagiarism, and the spread of misinformation. Strengthening and enhancing the moral and ethical competence of teachers is the key to the successful integration of ChatGPT in learning that aligns with the values of the Merdeka Curriculum.